An in-depth analysis of two common methodologies used to derive hourly solar radiation values from daily ones: pros and cons - Kambezidis, Harry D. (Frontiers in Environmental Science, 2025)
Solar radiation comprises the primary renewable source of energy on Earth and has so been exploited in the last 20 years. Despite this, solar radiation measurements are scarce worldwide, thus giving space to modelling. Nevertheless, modelling solar radiation at an hourly level is nowadays required for a short-term output forecast from solar installations. The daily global solar radiation decomposition models are one category of solar models that convert daily solar radiation values to hourly ones. The Collares-Pereira and Rabl (CPR) and Collares-Repeira, Rabl and Gueymard (CPRG) models have shown to provide a better performance than others at individual sites without exhibiting any sign of universality on the other hand. The current study looks at this gap. In this regard, twelve sites are selected around the world. To estimate hourly values, the CPR and CPRG models are applied to daily solar radiation estimates for each site in particular years. Hourly data sets that are openly accessible provide the daily values. Additionally, daily and monthly values are derived from the estimated and observed hourly values. The hourly, daily, and monthly scales are used to compare the two models’ performances. The CPR model outperforms the CPRG model across all sites and time scales. A universal coefficient of correction is used to further enhance the CPR performance, bringing the CPR-estimated solar radiation very close to the observed one.